Chelidonium majus crude extract inhibits migration and induces cell cycle arrest and apoptosis in tumor cell lines. (22nd August 2016) - Deljanin, Milena; Nikolic, Mladen; Baskic, Dejan; Todorovic, Danijela; Djurdjevic, Predrag; Zaric, Milan; Stankovic, Milan; Todorovic, Milos; Avramovic, Dusko; Popovic, Suzana
Abstract: Ethnopharmacological relevance: Chelidonium majus L (Papaveraceae) is widely used in alternative medicine for treatment of various disorders. Antitumor activities of alkaloids isolated from this plant have been reviewed, while there are only a few studies that examine properties of the whole extract. Aim of the study: The aim of the present study was to investigate direct cytotoxic effects, as well as indirect antitumor effects of Chelidonium majus ethanolic extract against different tumor cell lines, . Materials and methods: MTT and SRB assays were performed to estimate cytotoxic effects of Chelidonium majus extract against human tumor cell lines A549, H460, HCT 116, SW480, MDA-MB 231 and MCF-7 and peripheral blood mononuclear cells from healthy individuals. Cell cycle analysis was performed by flow cytometry. Type of cell death induced by extract was determined by flow cytometry and cell morphology assessment. Inhibitory effect on migration of cancer cells was assessed by wound healing assay. Results: Chelidonium majus extract showed selective time- and dose-dependent increase of cytotoxicity in all six cell lines, with individual cell line sensitivities. Extract promoted cell cycle arrest and induced apoptosis. Cotreatment with doxorubicin enhanced cytotoxicity of the drug. Also, inhibitory effect on migration was shown with non-toxic extract concentration. Conclusions: These results indicate possible usefulness of Chelidonium majus crude extract in antitumor therapy, whether through its direct cytotoxic effect, by prevention of metastasis, or as adjuvant therapy. Graphical abstract: